Correction: Bodea et al. Optimization of Moist and Oven-Dried Bacterial Cellulose Production for Functional Properties. Polymers 2021, 13, 2088 - Ioana M. Bodea (MDPI AG, 2021)
The authors wish to make a change to the published paper [...]